Sustainable and innovative biological control strategies against Pseudomonas syringae pv. tomato, Pseudomonas savastanoi pv. phaseolicola and Xanthomonas spp. affecting vegetable crops: a review - Giovanardi, Davide; Biondi, Enrico; Biondo, Nina; Quiroga, Nicolás; Modica, Francesco; Puopolo, Gerardo; Pérez Fuentealba, Set (Frontiers in Plant Science, 2025)
Genera Pseudomonas and Xanthomonas include bacterial species that are etiological agents of several diseases of major vegetable crops, such as tomato, pepper, bean, cabbage and cauliflower. The bacterial pathogens of those genera may cause severe crop damage, leading to symptoms like leaf spots, wilting, blights, and rotting. These plant pathogens can affect propagation materials and spread rapidly through plant tissues, contaminated soils, or water sources, making them challenging to control using conventional chemical products alone. Biopesticides, such as essential oils (EOs), are nowadays studied, tested and formulated by employing nano- and micro-technologies as innovative biological control strategies to obtain more sustainable products using less heavy metal ions. Moreover, there is a growing interest in exploring new biological control agents (BCAs), such as antagonistic bacterial and fungal species or bacteriophages and understanding their ecology and biological mechanisms to control bacterial phytopathogens. These include direct competition for nutrients, production of antimicrobial compounds, quorum quenching and indirect induction of systemic resistance. Optimisation of the biocontrol potential goes through the development of nanoparticle-based formulations and new methods for field application, from foliar sprays to seed coatings and root inoculation, aimed to improve microbial stability, shelf life, controlled release and field performance. Overall, the use of biological control in horticultural crops is an area of research that continues to advance and shows promising potential. This review aims to provide an in-depth exploration of commercially accessible biocontrol solutions and innovative biocontrol strategies, with a specific focus on the management of bacterial diseases in vegetable crops caused by Pseudomonas and Xanthomonas species. In this article, we highlighted the advancements in the development and use of EOs and other BCAs, emphasizing their potential or shortcomings for sustainable disease management. Indeed, despite the reduced dependence on synthetic pesticides and enhanced crop productivity, variable regulatory frameworks, compatibility among different BCAs, and consistent performance under field conditions are among the current challenges to their commercialization and use. The review seeks to contribute valuable insights into the evolving landscape of biocontrol in vegetable crops and to provide guidance for more effective and eco-friendly solutions against plant bacterial diseases.